Isoflurane inhalation regulated using positive system - Syam, Syafiie; Chong, P. K.; Chang, Jing Jing (IEEE, 2011)
The control of depth of anesthesia presents a very challenging and realistic control problem that calls for optimum, fast, and adaptable control algorithms. This system is a positive system where the state is never negative. The proposed controller possesses all qualities of a reliable control scheme, namely bounded control, impose positivity and optimum feedback gain finding. The controller is designed based on known patients' models. From simulation, the controller has shown the capability to drive the patient from a wake patient to general anesthesia by regulating isoflurane into the breathing system for controlling compartment site concentration that give BIS=50.